2022
DOI: 10.1002/bies.202100242
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acids movement and its relation to genome dynamics of repetitive DNA

Abstract: There is growing evidence of evolutionary genome plasticity. The evolution of repetitive DNA elements, the major components of most eukaryotic genomes, involves the amplification of various classes of mobile genetic elements, the expansion of satellite DNA, the transfer of fragments or entire organellar genomes and may have connections with viruses. In addition to various repetitive DNA elements, a plethora of large and small RNAs migrate within and between cells during individual development as well as during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 121 publications
0
0
0
Order By: Relevance
“…There is evidence that highly repeated mobile elements may play a certain role in the regulation of genetic activity (see for example (Rocha et al, 2022)), their distribution must also be taken into account in the epigenetic analysis (Lerat et al, 2019). It is important to note that evidence is accumulating about the important role that repeated mobile elements may play in horizontal gene transfer between phylogenetically distant species (Ahmad et al, 2021;Athanasouli, Rӧdelsperger, 2022;Kejnovsky, Jedlicka, 2022). Dodsworth et al (2015) have shown that a set of repeated elements contains a significant phylogenetic signal.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that highly repeated mobile elements may play a certain role in the regulation of genetic activity (see for example (Rocha et al, 2022)), their distribution must also be taken into account in the epigenetic analysis (Lerat et al, 2019). It is important to note that evidence is accumulating about the important role that repeated mobile elements may play in horizontal gene transfer between phylogenetically distant species (Ahmad et al, 2021;Athanasouli, Rӧdelsperger, 2022;Kejnovsky, Jedlicka, 2022). Dodsworth et al (2015) have shown that a set of repeated elements contains a significant phylogenetic signal.…”
Section: Introductionmentioning
confidence: 99%